Risk factors associated with repeat breeding in female aceh cattle in Pidie District, Indonesia - subagyo, djoko; Siregar, Tongku N.; Ferasyi, Teuku Reza; Rahayu, Sri; Masrianto, M. (The International Journal of Tropical Veterinary and Biomedical Research, 2025)
Background and Aim: Low reproductive efficiency, particularly repeat breeding, is a significant constraint in cattle production systems in Indonesia. Repeat breeding is defined as the failure of a cow to conceive after three or more services with fertile males, without detectable reproductive abnormalities. This study aimed to determine the prevalence of repeat breeding and identify risk factors related to reproductive and management practices in female aceh cattle in Pidie District.Materials and Methods: A cross-sectional observational study was conducted using simple random sampling. The study population consisted of Aceh cows that had undergone artificial insemination (AI), with data obtained from inseminator records. Primary data were collected through structured interviews with inseminators and farmers, while secondary data were sourced from AI service logs. Statistical analysis was performed using odds ratios (OR) to assess associations, followed by chi-square tests for significance (SPSS 2007).Results : The prevalence of repeat breeding in aceh cattle was 58.3%. Significant risk factors included poor estrus detection knowledge (P= 0.043; OR= 2.32), delayed estrus reporting (P= 0.076; OR= 1.90), inadequate management of pregnant cattle (P= 0.070; OR= 0.37), and improper placement of feed and water (P= 0.070; OR= 0.18). Strong associations were also found with poor water source quality (P= 0.001; OR= 3.97) and prepartum confinement practices (P= 0.000; OR= 0.20).Conclusion: In contrast, general husbandry practices, including housing hygiene, floor type, and drainage, showed no significant impact. This study highlights the urgent need for improved farmer awareness and better reproductive management to reduce repeat breeding in aceh cattle.